A Syntactic Analysis of Quranic Language - BENMECHTA, Karima (My University, 2020)
This dissertation explores the application of Van Valin’s theory of Role and Reference Grammar (RRG) on the Quranic language, particularly surat Al-kahf. The purpose of this study is to analyse the syntactic structure of the selected verses from surat Al-kahf for the subsequent three objectives. The first objective is to investigate the extent to which these verses adhere to RRG principles. The second objective is to examine the type of clause-linkage existing within this surah, whereas the third is to investigate the association of the semantic content to the structural representation, that is, to study the unity of the surah. In order to provide answers to these inquires, the study adopts a qualitative method wherein a syntactic analysis is conducted on ten selected verses from surat Al-kahf (Q18: 59-64 and 82-87). These verses were, then, divided into sentences for the sake of facilitating the process of application of the Layered Structure Clause (LSC) of RRG. In this context, the findings suggest that most of the sentences of the selected verses obeyed RRG’s model, with few cases of violation and alternation. Moreover, the results depicted an integral unity within the surah. In conclusion, the Quranic language adheres to Van Valin’s model to a considerable extent. On this basis, a meticulous analysis of the LSC with the inclusion of both the operators and focus projection is recommended for further insights on the structure of Quranic language.
A Role and Reference Grammar Approach of Surat al Kahf
Keywords: Van Valin; RRG; Quranic language; LSC; Syntactic structure; Clause-linkage; Surat Al-kahf